Hematological Parameters Alteration in Thai Garlic Farmers Exposed to Mixed Pesticides - Chepatee Srilesin; Jirapak Ruttanapattanakul; Yutti Amornlertwatana; Rangsan Watcharakawin; Churdsak Jaikang (Institute of Medico-legal Publications Pvt Ltd, 2022)
Fungicides, herbicides, and insecticides are commonly agrochemicals used to eliminate pests during garliccultivation. Occupational exposure to mixed pesticides can cause hematological abnormalities. The aim of thisstudy was toassess the adverse effects of chronic mixed pesticide exposure in the garlic farmers by using thehematological parameters. The blood sample was collected from 137 Thai farmers who chronically exposed tomixed pesticide and 59 control group who were not a history of exposure to mixed pesticide. Complete BloodCount (CBC) analysis was performed to investigate the hematological parameters alteration pattern of Thaifarmers. Statistical analysis also performed by using Mann-Whitney U test. Our investigations revealed thatthemean values of white blood cell (WBC) count, lymphocyte, basophil, platelet distribution width, mean plateletvolume and platelet large cell ratio significantly decreased in the chronic exposed group but did not affect whencompared with the normal reference ranges. The results clearly demonstrated that chronic exposure to the mixedpesticides during garlic cultivation alters the hematological parameters. The farmers should be aware and checktheir health to prevent the adverse effects from pesticide intoxication.